Feasibility Study of Investment in New Conveyor Facility for CHF Supply Power Plant ABC PT XYZ - Riana Muhammad Sutandar; Taufik Faturohman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
PLTU ABC is a coal-fired steam power plant that receives its coal supply from PT XYZ. At present, coal delivery relies on a single conveyor system with a capacity of 1,200 tons per hour. Since PT XYZ supplies coal based on the power plant’s demand, the conveyor must remain operational 24 hours a day. Any unplanned maintenance on the conveyor can disrupt supply and result in lost electricity production. Monthly coal delivery targets have been established, necessitating alternative delivery methods in case the conveyor system fails. Three alternative solutions have been identified: leasing a temporary conveyor, investing in a new conveyor system, or switching to direct coal delivery via trucks. The capital expenditure estimates are based on historical purchase data, adjusted for inflation over the past five years. The financial analysis indicates that direct truck delivery offers the highest return on investment and stronger cash flow compared to either leasing or constructing a new conveyor system. The project’s financial metrics include a Net Present Value (NPV) of IDR 51.22 billion, an Internal Rate of Return (IRR) of 60.13%, a Modified Internal Rate of Return (MIRR) of 24.54%, and a payback period of 1.55 years. Further validation using sensitivity analysis, scenario analysis, and Monte Carlo simulations showed that the probability of achieving a positive NPV (NPV > 0) is 65%. Based on these findings, it is concluded that direct delivery by trucks is more financially viable than investing in or leasing conveyor facilities.